Identification of wearing comfort of the textile uppers of commercial footwear - Kaziur, Patrycja; Mikołajczyk, Zbigniew; Matusiak, Małgorzata (Wydawnictwo Politechniki Łódzkiej, 2022)
Knitting technologies have contributed to the production of textile footwear not only to reduce waste, but also to increase their physiological comfort. In this study, the functional properties of twelve commercially available knitted uppers and two footwear leathers were identified. For each of the tested variants, the following parameters were determined: thickness, mass per square meter, air and water vapor permeability, and selected parameters related to the thermal insulation and moisture sorption. On the basis of conducted research, it was shown that the best parameters were characteristic for knitted fabrics with jacquard weaves produced on cylindrical crocheting machines of large diameters.
Keywords: footwear; comfort; footwear uppers; microclimate; knitted fabrics; obuwie; komfort; cholewki obuwia; mikroklimat; dzianiny